Effect of Sacubitril/Valsartan on Exercise-Induced Lipid Metabolism in Patients With Obesity and Hypertension. Issue 1 (January 2018) - Engeli, Stefan; Stinkens, Rudi; Heise, Tim; May, Marcus; Goossens, Gijs H.; Blaak, Ellen E.; Havekes, Bas; Jax, Thomas; Albrecht, Diego; Pal, Parasar; Tegtbur, Uwe; Haufe, Sven; et al.
Abstract : Sacubitril/valsartan (LCZ696), a novel angiotensin receptor-neprilysin inhibitor, was recently approved for the treatment of heart failure with reduced ejection fraction. Neprilysin degrades several peptides that modulate lipid metabolism, including natriuretic peptides. In this study, we investigated the effects of 8 weeks' treatment with sacubitril/valsartan on whole-body and adipose tissue lipolysis and lipid oxidation during defined physical exercise compared with the metabolically neutral comparator amlodipine. This was a multicenter, randomized, double-blind, active-controlled, parallel-group study enrolling subjects with abdominal obesity and moderate hypertension (mean sitting systolic blood pressure ≥130–180 mm Hg). Lipolysis during rest and exercise was assessed by microdialysis and [1, 1, 2, 3, 3- 2 H]-glycerol tracer kinetics. Energy expenditure and substrate oxidation were measured simultaneously using indirect calorimetry. Plasma nonesterified fatty acids, glycerol, insulin, glucose, adrenaline and noradrenaline concentrations, blood pressure, and heart rate were also determined. Exercise elevated plasma glycerol, free fatty acids, and interstitial glycerol concentrations and increased the rate of glycerol appearance. However, exercise-induced stimulation of lipolysis was not augmented on sacubitril/valsartan treatment compared with amlodipine treatment. Furthermore, sacubitril/valsartan did not alter energy expenditure and substrate oxidation during exercise compared with amlodipine treatment. In conclusion, sacubitril/valsartan treatment for 8 weeks did not elicit clinically relevant changes in exercise-induced lipolysis or substrate oxidation in obese patients with hypertension, implying that its beneficial cardiovascular effects cannot be explained by changes in lipid metabolism during exercise. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01631864. Abstract : Supplemental Digital Content is available in the text.